2007
DOI: 10.1038/nm1624
|View full text |Cite
|
Sign up to set email alerts
|

Broad HIV-1 neutralization mediated by CD4-binding site antibodies

Abstract: We have identified several patient sera showing potent and broad HIV-1 neutralization. Using antibody adsorption and elution from selected gp120 variants, the neutralizing specificities of the two most broadly reactive sera were mapped to the primary receptor CD4-binding region of HIV-1 gp120. Novel antibodies to the CD4-binding site are elicited in some HIV-1-infected individuals, and new approaches to present this conserved region of gp120 to the immune system may result in improved vaccine immunogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
435
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(454 citation statements)
references
References 16 publications
(1 reference statement)
18
435
0
Order By: Relevance
“…The beads were then pelleted by centrifugation, and the Protein A-depleted fraction was collected. Serum adsorptions with antigen-coupled beads were performed using tosyl-activated magnetic beads, as described previously (25). A total of 1 mg of gp120 or 1 mg of TM-Pst1 was used for bead coupling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The beads were then pelleted by centrifugation, and the Protein A-depleted fraction was collected. Serum adsorptions with antigen-coupled beads were performed using tosyl-activated magnetic beads, as described previously (25). A total of 1 mg of gp120 or 1 mg of TM-Pst1 was used for bead coupling.…”
Section: Methodsmentioning
confidence: 99%
“…Two rounds of adsorption were performed to ensure complete removal of antigen-specific antibodies. Functional antibodies were eluted from beads by exposing the beads to series of increasingly acidic conditions, as described (25).…”
Section: Methodsmentioning
confidence: 99%
“…Altogether, these results indicated that CXCL4 interacts with a region of the gp120 outer domain located proximal to the CD4-BD, but not directly overlapping with this domain. To further confirm the lack of identity between the binding sites of CXCL4 and CD4 in gp120, we tested a mutated gp120 bearing the D368R substitution that abrogates interaction with CD4 (29) showing that it was coimmunoprecipitated by CXCL4 with similar efficiency as wild-type gp120 (Fig. S8).…”
Section: Cd4 + T Cells Was Not Downmodulated Upon Treatment With Cxcl4mentioning
confidence: 99%
“…In certain HIV-1-infected individuals, it has been found that neutralization is exclusively or substantially mediated by CD4 binding site antibodies (42,43). Previous attempts to focus the immune response toward the b12 epitope were done in the context of whole gp120 by introducing mutations to selectively diminish non-neutralizing antibody binding and adding glycosylation sites to dampen responses to regions outside the CD4bs (14 -16).…”
Section: Discussionmentioning
confidence: 99%